Proteasome inhibition induces DNA methylation alteration by attenuating the synthesis of DNA methyltransferase 1 and 3B in colorectal cancer - Wenwen Zhou; Yuling Sheng; Dingxue Hu; Yunyun An; Mengqi Yang; Wanqiu Wang; Shiva Basnet; Jingyu Yan; Shuxia Zhang; Qi Liu; Yunze Li; Yi Tan; et al. (Scientific Reports)
Abstract Proteasome is an essential organelle responsible for maintaining cellular protein homeostasis, but its relationship with DNA methylation remains unknown. In this study, we assessed DNA methylation of colorectal cancer (CRC) cells following treatment with proteasome inhibitors, and investigated the underlying mechanism of DNA methylation changes and the biological effects on CRC cells. We established that inhibition of proteasome leads to significant alterations in DNA methylation profile in CRC by suppressing the synthesis of DNA methyltransferases (DNMTs). We found that treating CRC cells with proteasome inhibitors results in attenuated translation of DNMT1 and DNMT3B, mediated by the inactivation of AKT and mammalian target of rapamycin (mTOR), which is dependent on the accumulation of p300, an acetyltransferase that inhibits AKT through acetylation modification. Furthermore, we demonstrated that downregulation of DNMT1 and DNMT3B confers protection against proteasome inhibitor treatment, potentially through reprogramming the transcriptome of CRC cells, highlighting the significant role of DNMTs in response to disruptions in protein homeostasis. Interestingly, it appears that the proteasome inhibitor-induced downregulation of DNMT1 and DNMT3B is specific to CRC. Altogether, our findings reveal an epigenetic effect of proteasome on DNA methylation in CRC through its regulation of DNA methyltransferase synthesis.